POLG1-Related Epilepsy: Review of Diagnostic and Therapeutic Findings - Specchio, Nicola (Brain Sci, 2020)
Background: The clinical spectrum associated with POLG1 gene mutations ranges from non-syndromic epilepsy or mild isolated neurological signs to neurodegenerative disorders. Our aim was to review diagnostic findings, therapeutic approaches and outcomes of reported cases of epilepsy related to POLG1 mutation. Methods: The articles for review were identified through a systematic research on PubMed and EMBASE databases from January 2003 to April 2020, searching for the terms “Epilepsy AND POLG OR polymerase gamma,” OR “POLG1”. Results: Forty-eight articles were selected for review, which included 195 patients. Two main peaks of age at epilepsy onset were found: at ages 1 and 13 years. The most frequent seizure type was myoclonic. The occurrence of Status Epilepticus was reported in 46.4% of cases. Epileptiform and slow abnormalities were most frequently seen over occipital regions. Brain Magnetic Resonance Imaging (MRI) revealed increased T2 signal intensities in thalamic regions. Genetic analysis revealed a prevalence of A467T, W748S and G848S (74.2% of patients) mutations. Survival at 5 years was estimated at very low levels (30.2% of patients). Conclusion: In this review, we included cases with both pediatric and adult epilepsy onset. The analysis of data regarding prognosis showed that survival is related to age at onset of epilepsy.